ChemInform Abstract: Asymmetric Total Synthesis of Mycoleptodiscin A. Issue 39 (September 2015) - Zhou, Shupeng; Chen, Hao; Luo, Yijie; Zhang, Wenhao; Li, Ang
Abstract The first total synthesis of the indolosesquiterpenoid mycoleptodiscin A is described.